Brand Loyalty Based on Social Media Marketing, Brand Awareness, and Customer Satisfaction at Kulo Coffee Shop - Erny Amriani Asmin; Yulianingsih; Annisa Dwi Rahayu (University of Merdeka Malang, 2025)
The purpose of this research is to examine the relationship between brand loyalty and consumer happiness, with consumer happiness serving as a mediator between brand recognition and social media marketing. To provide a comprehensive understanding of the relationships among the variables, the research employs both descriptive and associative approaches. The people who will be studied are the customers of Generation Z who go to Kulo Cafe in Bogor. Via specific criteria relating to the study's aims, a sample of 100 respondents was selected via purposive sampling. For this data study, we turned to path analysis, which lets us look at the interplay between variables in several ways. The results show that raising brand awareness and promoting social media campaigns significantly improve consumer happiness and loyalty. This shows that highly recognizable brands and effective social media marketing strategies may increase customer happiness, which in turn increases brand loyalty among millennials and Generation Z. Further evidence that consumer pleasure plays a crucial mediating role in the relationship between brand loyalty and other outcomes is provided by the results. Social media marketing, brand awareness, and customer loyalty are all interconnected via the idea that satisfied consumers are more likely to remain loyal to the business. A combination of brand management strategies and digital marketing campaigns is essential for strengthening relationships with customers and retaining their loyalty, as shown by these findings.